DIVERSITY OF BUTTERFLIES (INSECTA: LEPIDOPTERA) IN AND AROUND SANDUR TALUK, BELLARY DISTRICT, KARNATAKA - HEGDE, SNEHA SUMA; SADIQUA, ANJUM; SWATHI, .; GURURAJA, . (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
A study of butterfly diversity was conducted during Sep 2019- Feb 2020 using Line transect count method to assess the species diversity in Sandur taluk, Bellary district, Karnataka. Habitat destruction in terms of mining activity can be a potential threat to this area and is expected to be the reason for reduction in the abundance of butterfly species in the study area. The present study was undertaken to document the species diversity of butterflies and explore the existing diversity of butterflies. A Total 56 species of butterflies belonging to 05 families, namely, Nymphalidae, Papilionidae, Pieridae, Lyncaenidae and Hesperiidae were recorded. This is the first study on butterfly diversity in this area. Our aim is to explore and document butterfly fauna, which will be a useful platform for conservation of butterflies and quantitative study of diversity.